A mobile application for patient engagement to support interdisciplinary care - Haux, Christian; Lutyj, Julia; Seitz, Max; Knaup-Gregori, Petra (MEDINFO 2019, 2019)
There is evidence on interrelationships between several dental and chronic diseases. However, dentists and general practitioners often lack information when treating such multimorbid patients. Engagement of the patient in the decision making process may help to fill this gap and improve intersectoral care. The DentPrevent project therefore aims to develop a mobile application that can be used by patients to report information about their health status for interdisciplinary care. In this paper, the user interface concept and evaluation of the prototype of this mobile application is presented.
Gesehen am 08.12.2020